PELATIHAN TENTANG PENYUSUNAN PROPOSAL DAN LAPORAN PENELITIAN TINDAKAN KELAS PADA GURU SEKOLAH DASAR GUGUS KI HAJAR DEWANTORO DABIN I KECAMATAN TUGU KOTA SEMARANG - Ansori, Purnomo, Isa (Universitas Negeri Semarang, 2017)
The purpose of this service activities to:. (1) improving and describe the teacher's knowledge of the preparation of research proposals and reports a class action research, (2) improve and describe the ability of teachers in preparing classroom action research, (3) .mendeskripsikan response of teachers to training on proposal preparation and classroom action research report.This service activities using training methods. The target audience of this service activities are elementary teachers Force Ki Hajar Devantoro Dabin I districts Tugu Semarang. Method of service activities that are used to achieve the purpose of service activities is a training technique. Implementation of community service activities is carried out through four stages, namely: (1) planning, (2) the stage of implementation of activities, (3) the stage of observation activities, (4) the stage of reflection activities and closing activities. Evaluation used in community service activities using techniques written assessment, performance assessment, and assessment of products. Evaluation tools used include achievement test, observation sheets, questionnaires.The results of service activities showed: (1) Some 90% of primary school teachers after receiving training, are knowledgeable about the preparation of proposals and reports of classroom action research, in both categories, meaning that it has control of a number of 71 s / d 85% on the preparation of research proposals and reports class actions research, with an average score of 80.9667 means well; (2) Some 76.67% of elementary school teachers after receiving training, have the ability to develop a proposal a class action research, in the excellent category, meaning that it has the capability mastery class action proposal 81.25 s / d 100%, with an average score 83.1 means excellent; (3) Some 73.33% of elementary school teachers have a very good response to the training in writing research proposals and reports a class action research, meaning that it has a very positive attitude and strongly agree (scale 3 and 4 is greater than the scale 1 and 2) for the preparation of proposals and reports of classroom action research, with an average score of 33.80 means very good (scale 3 and 4 is greater than the scale 1 and 2).The suggestions put forward relating to the results of the devotion, among others: (1) to improve the professionalism of teachers, especially the ability of teachers in the preparation of proposals and reports of classroom action research, the need for further training on the preparation of proposals and reports of classroom action research, for teachers SD / MI, (2) LPTK, especially PGSD UNNES need to increase community services for professors to conduct training on the preparation of proposals and reports of classroom action research, for teachers SD / MI.